urgency of slowness (Devenires, 2025)
This essay aims to address the diagnosis of the illness of our time, which, curiously, takes the form of a temporal pathology, and, at the same time, to explore the alternative of slowness (not merely as a modulation of speed, but as a virtue, pathos, and way of life).